Simulation-Based Education to Train Learners to "Speak Up" in the Clinical Environment: Results of a Randomized Trial. Issue 6 (December 2018) - Oner, Ceyda; Fisher, Nelli; Atallah, Fouad; Son, Mary Ann; Homel, Peter; Mykhalchenko, Katerina; Minkoff, Howard
Abstract : Introduction: Assertiveness is essential for communication and/or speaking up. We performed a randomized trial to assess the effectiveness of assertiveness/advocacy/CUS/two-challenge rule (AACT) simulation-based education for labor and delivery, as well as postpartum nurses. We aimed to determine whether this training would improve labor and delivery and postpartum nurses speaking up in the clinical setting. Methods: We conducted a randomized controlled trial among nurses on labor and delivery and postpartum units. During the intervention, participants were trained on abnormal vital signs, underwent a baseline assertiveness self-assessment, and were block-randomized (by work location: labor and delivery or postpartum) to either simulation-based AACT (intervention) or I-PASS [Illness Severity, Patient Summary, Action List, Situational Awareness and Contingency Planning, Synthesis by Receiver hand-off tool education] (control) simulation-based education. The outcome part of the study consisted of an in situ simulated clinical encounter during which each individual learner's assertive behaviors were assessed as they found out about a patient's abnormal vital signs. Two raters, different from those that participated in the intervention part of the experiment, and who were blinded to whether the learner was in the control or intervention arm, scored participants. The learner (Registered Nurse) was not aware that this was an in situ simulation and perceived this as a real clinical encounter. The degree to which the learners spoke up was measured using a validated scale (Pian-Smith). Results: Seventy nurses completed the study. There were 34 learners in the intervention and 36 in the control groups. Among those in the intervention group, there were 18 labor and delivery (LDI) nurses and 16 postpartum (PPI) nurses. Among the control group, there were 14 labor and delivery (LDC) nurses and 22 postpartum (PPC) nurses. Using a five-point Pian-Smith scale, we demonstrated that there was no difference in the likelihood of speaking up between the overall intervention and control groups (2.00 ± 1.00 and 1.65 ± 0.82, P = 0.10). Among controls, the likelihood of speaking up was higher for labor and delivery nurses than for postpartum nurses ( P < 0.006). There was a significant interaction ( P = 0.02) between treatment group and work location. Although the control and intervention groups from labor and delivery showed similar higher levels of speaking up (2.29 ± 0.89 and 2.06 ± 0.95, respectively, P = 0.49), postpartum nurses in the intervention arm were more likely to speak up than were postpartum nurses in the control arm (1.97 ± 1.07 vs. 1.25 ± 0.43, P = 0.007). Conclusions: Although there was no difference in speaking up scores between intervention and control groups overall, simulation-based AACT training among postpartum nurses was associated with a statistically significant increase in the likelihood of speaking up during a challenging simulated clinical encounter. The degree of change makes the clinical significance uncertain. There was no statistically significant difference in the likelihood of speaking up among labor and delivery nurses. Abstract : Supplemental digital content is available in the text.